ANALYSIS OF WORK CONDITIONS AND CAUSES OF WEAR HOLES SEPARATING SIEVES IN SERVICE - Федченко, З. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Many scientists involved in improving the work of separating containing novelty but reduce the overall reliability of the crusher. The article presents the main damage of separating sieves crushers; which leads to ineffective grinding grain mass. The physical nature of the wear of the separating sieves practically not been studied; as a consequence of the complexity of the structure of their working surfaces. The main hypothesis of the causes of the wear surfaces is the influence of the flow of the grain mixture and a small amount of abrasive particles having a hardness greater than the hardness of the material of the sieve. Given the characteristics of the separation of the screens; as perforated detail; and specific features of the wear holes; are promising for improving the resource should be considered a search; above all; constructive methods of increasing durability. This is due to the operating conditions and manufacturing of the screens; where the use of hardening wear resistant coatings or materials is not technically feasible and economically justified.One such approach is a constructive method provides for the fabrication of sieves with more resistant to wear and form holes.